2013
DOI: 10.11591/edulearn.v7i3.179
|View full text |Cite
|
Sign up to set email alerts
|

Computer Anxiety, Academic Stress, and Academic Procrastination on College Students

Abstract: Prokrastinasi akademik merupakan gejala yang umum terjadi di kalangan mahasiswa. Kurangnya pemahaman dalam menggunakan teknologi komputer dapat menimbulkan kecemasan dalam pengoperasian komputer, sedemikian sehingga menyebabkan penangguhan dalam menyelesaikan tugas-tugas perkuliahan yang berhubungan dengan operasi komputer. Di sisi lain, kegagalan dalam mencapai sasaran akademis tertentu sebagaimana diharapkan oleh orangtua dan/atau mahasiswa yang bersangkutan juga membuat mahasiswa kurang fokus dan menimbulka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
19
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 21 publications
6
19
0
2
Order By: Relevance
“…These researchers highlighted the salience of the relationship between academic stress and general stress in activities such as test taking, homework, and class participation. In addition, researchers have found significant differences between male and female students' levels of academic stress (Backović et al, ; Misra & McKean, ; Rahardjo et al, ), highlighting important gender differences in college student development. Researchers have found that coping responses are important for college students' development (e.g., engaging in positive reframing, taking action, seeking support; Cavazos, Johnson, & Sparrow, ; Lazarus & Folkman, ) and become problematic when stress outweighs coping resources and mechanisms (e.g., life satisfaction, locus of control).…”
Section: Academic Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…These researchers highlighted the salience of the relationship between academic stress and general stress in activities such as test taking, homework, and class participation. In addition, researchers have found significant differences between male and female students' levels of academic stress (Backović et al, ; Misra & McKean, ; Rahardjo et al, ), highlighting important gender differences in college student development. Researchers have found that coping responses are important for college students' development (e.g., engaging in positive reframing, taking action, seeking support; Cavazos, Johnson, & Sparrow, ; Lazarus & Folkman, ) and become problematic when stress outweighs coping resources and mechanisms (e.g., life satisfaction, locus of control).…”
Section: Academic Stressmentioning
confidence: 99%
“…The study included not only cognitive factors that affect academic stress but also gender as a biological factor. Previous researchers have shown that female students have higher levels of academic and general stress compared with their male counterparts (Backović, Živojinović, Maksimović, & Maksimović, ; Misra & McKean, ; Rahardjo, Juneman, & Setiani, ). Our study differentiated from existing research focusing on achievement motivation, life satisfaction, and locus of control by including cognitive factors and gender as a biological factor in relation to academic stress.…”
mentioning
confidence: 98%
“…Salah salah satu penyebab keterlambatan dalam menyelesaikan skripsi dikarenakan adanya perilaku menunda-nunda dalam area akademik atau yang dikenal dengan istilah prokrastinasi akademik. Yong (Rahardjo, Juneman & Setiani, 2013) mengemukakan bahwa prokrastinasi akademik dapat ditemukan dikalangan mahasiswa, baik mahasiswa dari lembaga publik maupun mahasiswa dari lembaga swasta. Lee (2005) mengemukakan bahwa mahasiswa kadang lupa waktu ketika melakukan suatu kegiatan, termasuk dalam kegiatan keorganisasian.…”
Section: Pendahuluanunclassified
“…Rahardjo et al found that students in both private and public universities had a similar level of procrastination [6]. Alternatively, the university types contribute insignificant effect to the student's procrastination.…”
Section: Introductionmentioning
confidence: 98%
“…Rahardjo, Juneman, and Setiani understand that students in higher education exert their energy to complete their degrees [6]. However, if the students are unable to control their excessive procrastination, it possibly leads to severe mental health problems [11].…”
Section: Introductionmentioning
confidence: 99%